Childhood exposure to emotional abuse and later life stress among Kenyan women: a mediation analysis of cross-sectional data. Issue 4 (4th July 2017) - Goodman, Michael L.; Gutarra, Claudia; Billingsley, Katherine M.; Keiser, Philip H.; Gitari, Stanley
ABSTRACT: Background and objective: We explore whether perceived stress among Kenyan mothers is predicted by childhood exposure to emotional abuse – both witnessed among parents and experienced directly. Further, we explore whether this association is mediated by social support, family functioning and polygynous marriage. Design: We used cross-sectional data from a systematic random sample ( n = 1974) of mothers in semi-rural Kenya. Methods: Data were collected using validated scales and trained interviewers. Analyses were conducted using bootstrapped structural equation models and fixed-effects linear regression models, controlling for age and household wealth. Results: Reported experience of emotional abuse – both directly experienced and observed among household adults – was high in the present population (72.5% and 69%, respectively). Perceived stress among women was significantly higher if they were exposed to more emotional abuse during childhood ( p < .001). Lower social support, worse family functioning and higher rates of polygynous marriage mediated pathways between emotional abuse exposure during childhood and adult perceived stress. Conclusion: Future research should investigate whether social integration, identity formation and self-esteem underlie observed dynamics in sub-Saharan Africa. Efforts to promote social integration and support should target children currently experiencing emotional abuse, and may include child-targeted high quality television programing and adult-targeted media and celebrity campaigns.